Metabolically Distinct Pools of Phosphatidylcholine Are Involved in Trafficking of Fatty Acids out of and into the Chloroplast for Membrane Production. Issue 11 (11th September 2019) - Karki, Nischal; Johnson, Brandon S.; Bates, Philip D.
Abstract : Chloroplast lysophosphatidylcholine acyltransferases are involved in PC acyl editing with newly synthesized fatty acids, and not in lysophosphatidylcholine transport for galactolipid synthesis. Abstract: The eukaryotic pathway of galactolipid synthesis involves fatty acid synthesis in the chloroplast, followed by assembly of phosphatidylcholine (PC) in the endoplasmic reticulum (ER), and then turnover of PC to provide a substrate for chloroplast galactolipid synthesis. However, the mechanisms and classes of lipids transported between the chloroplast and the ER are unclear. PC, PC-derived diacylglycerol, phosphatidic acid, and lyso-phosphatidylcholine (LPC) have all been implicated in ER-to-chloroplast lipid transfer. LPC transport requires lysophosphatidylcholine acyltransferase (LPCAT) activity at the chloroplast to form PC before conversion to galactolipids. However, LPCAT has also been implicated in the opposite chloroplast-to-ER trafficking of newly synthesized fatty acids through PC acyl editing. To understand the role of LPC and LPCAT in acyl trafficking we produced and analyzed the Arabidopsis ( Arabidopsis thaliana ) act1 lpcat1 lpcat2 triple mutant. LPCAT1 and LPCAT2 encode the major lysophospholipid acyltransferase activity of the chloroplast, and it is predominantly for incorporation of nascent fatty acids exported form the chloroplast into PC by acyl editing. In vivo acyl flux analysis revealed eukaryotic galactolipid synthesis is not impaired in act1 lpcat1 lpcat2 and uses a PC pool distinct from that of PC acyl editing. We present a model for the eukaryotic pathway with metabolically distinct pools of PC, suggesting an underlying spatial organization of PC metabolism as part of the ER–chloroplast metabolic interactions.